Hypercyclic composition operators on Hilbert spaces of analytic functions - Zagorodnyuk, A. V.; Mozhyrovska, Z. H. (Methods of Functional Analysis and Topology, 2014)
In the paper we consider composition operators on Hilbert spaces of analytic functions of infinitely many variables. In particular, we establish some conditions under which composition operators are hypercyclic and construct some examples of Hilbert spaces of analytic functions which do not admit hypercyclic operators of composition with linear operators.